Design and assessment of psychometric features of life skills inventory - Ali Fathi Ashtiani; Seyed Mohammad Afzali; Abbas Ebadi; Hamidreza Hassanabadi (Wolters Kluwer Medknow Publications, 2018)
Introduction: The importance of life skills and their application in promoting personal, family, and occupational health in military personnel is well recognized. It is, therefore, important to identify and assess life skills in military personnel with a valid and reliable tool. The present study aims to develop such a tool and evaluate its psychometric features in military personnel. Materials and Methods: As part of a mixed study, a qualitative concept analysis study was conducted using hybrid approach to redefine life skills in military personnel, and results obtained were used to form a pool of items. Next, in a methodological study, psychometric evaluation, qualitative and quantitative face validity, qualitative and quantitative content validity, and construct validity (exploratory factor analysis), and reliability (using test-retest and internal consistency) were performed on the inventory. Results: Initial pool of items was designed with 156 items, which were reduced to 93, following qualitative face validity, and further reduced to 80 after quantitative face validity (item impact score). No further reduction was implemented after qualitative and quantitative content validity (content validity ratio and content validity index ratio). Following construct validity (factor analysis), the remaining 80 items were summarized in 5 factors. Cronbach's alpha for the 5 factors was found 0.7, and correlation coefficient of test-retest results exceeded 0.9 and was significant at 0.01. Conclusion: Given the acceptable results of psychometric features, this tool can be used as a valid and reliable tool for assessing life skills in military personnel.